2013
DOI: 10.4034/rbcs.2013.17.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos Níveis de Ansiedade em Pacientes Submetidos ao Tratamento Odontológico

Abstract: RESUMO Introdução:A ansiedade é um estado subjetivo de sentimento ou reação perante uma situação desconhecida, e quando o sentimento de ansiedade ocorre diante da perspectiva ou em relação ao tratamento odontológico, tem sido chamado de ansiedade odontológica. Objetivo: A proposição deste trabalho foi avaliar a prevalência de ansiedade ao tratamento odontológico de pacientes atendidos na Clínica Integrada do Curso de Odontologia da Universidade Federal da Paraíba. Metodologia: A amostra foi composta por 60 pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
14

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 4 publications
1
10
0
14
Order By: Relevance
“…In the literature, the influence of these variables on anxiety differs among the studies. Pereira et al [25] conducted a study with 60 patients, using the DASS scale to determine the presence anxiety and found no significant differences in anxiety with reference to gender and age-range. On the other hand, Paryab and Hosseinbor [26].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the influence of these variables on anxiety differs among the studies. Pereira et al [25] conducted a study with 60 patients, using the DASS scale to determine the presence anxiety and found no significant differences in anxiety with reference to gender and age-range. On the other hand, Paryab and Hosseinbor [26].…”
Section: Discussionmentioning
confidence: 99%
“…O medo pode ser conceituado como um temor a algo ou alguma coisa que é externo e que se apresenta como um perigo real, que ameaça a integridade física ou psicológica da pessoa. O medo também é visto como um estado emocional de alerta ante o perigo, caracterizado por um conhecimento intelectual do mesmo, enquanto ansiedade está ligada a uma resposta emocional interna não facilmente reconhecível, com períodos de maior duração 2,4 .…”
Section: Introductionunclassified
“…Dental anxiety is preceded and followed by emotional reactions which are reflected in the presence of vital signs out the normal range [4], such as elevation of blood pressure and heart rate frequency, as well as changes in blood oxygen saturation [5].…”
Section: Introductionmentioning
confidence: 99%